Adversity in early childhood: Long-term effects on early academic skills. (March 2022) - Oeri, Niamh; Roebers, Claudia M.
Abstract: Background: The dimensional adversity model (McLaughlin & Sheridan, 2016) proposes that deprivation and threat affect child development differently. However, empirical support for the dimensional adversity model stems predominately from adolescent samples. Objective: We aimed to examine if deprivation and threat experiences in infancy have differential effects on pre-academic skills in early childhood. Furthermore, we addressed the effect of chronic vs. temporary adversity exposure in infancy. Participants and Setting: The population-based sample consisted of 3481 infants (49% girls). New-borns and their families were followed longitudinally (6 months to 6 years of age). Methods: Based on parental information, we computed four deprivation variables and three threat variables. Pre-academic cognitive and social-emotional skills were measured with a math and a vocabulary test and parental questionnaires on emotion regulation and behavioral problems. Results: Results showed that infant deprivation (but not threat) is negatively associated with math scores ( β  = −0.06) and language skills ( β  = −0.04) in kindergarten. However, infant threat and deprivation were both associated with behavioral problems ( β  = 0.06; β  = 0.04) and emotion-regulation difficulties ( β  = 0.04; β  = 0.03) in kindergarten. Analyses comparing chronic vs. temporary adversity exposure showed that chronic exposure was strongly related to all cognitive and social-emotional outcomes. Conclusions: We found partial support for the differential effects of deprivation and threat on pre-academic skills. Furthermore, the results suggest that particularly chronic adversity poses a potential risk for development - across domains of cognition and emotions. Highlights: Childhood adversity can be studied along the dimensions of deprivation and threat. The study examined if deprivation and threat in infancy have differential effects on early childhood outcomes. Infant deprivation (but not threat) was negatively associated with math and language skills in kindergarten. Infant threat and deprivation were associated with behavioral problems and emotion-regulation difficulties in kindergarten.